Hits-to-lead optimization of the natural compound 2,4,6-trihydroxy-3-geranyl-acetophenone (tHGA) as a potent LOX Inhibitor: synthesis, structure-activity relationship (SAR) study and computational assignment - Ng, Chean Hui; Rullah, Kamal; Abas, Faridah; Lam, Kok Wai; Ismail, Intan Safinar; Jamaludin, Fadzureena; Shaari, Khozirah (MDPI, 2018)
A new series of 2,4,6-trihydroxy-3-geranyl-acetophenone (tHGA) analogues were synthesized and evaluated for their lipoxygenase (LOX) inhibitory activity. Prenylated analogues 4a–g (half maximal inhibitory concentration (IC50) values ranging from 35 μ M to 95 μ M) did not exhibit better inhibitory activity than tHGA (3a) (IC50 value: 23.6 μ M) due to the reduction in hydrophobic interaction when the alkyl chain length was reduced. One geranylated analogue, 3d, with an IC50 value of 15.3 μ M, exhibited better LOX inhibitory activity when compared to tHGA (3a), which was in agreement with our previous findings. Kinetics study showed that the most active analogue (3e) and tHGA (3a) acted as competitive inhibitors. The combination of in silico approaches of molecular docking and molecular dynamic simulation revealed that the lipophilic nature of these analogues further enhanced the LOX inhibitory activity. Based on absorption, distribution, metabolism, excretion, and toxicity (ADMET) and toxicity prediction by komputer assisted technology (TOPKAT) analyses, all geranylated analogues (3a–g) showed no hepatotoxicity effect and were biodegradable, which indicated that they could be potentially safe drugs for treating inflammation